Novel large-scale chromosomal transfer in Bacteroides fragilis contributes to its pan-genome and rapid environmental adaptation. Issue 11 (14th November 2017) - Husain, Fasahath; Tang, Kevin; Veeranagouda, Yaligara; Boente, Renata; Patrick, Sheila; Blakely, Garry; Wexler, Hannah M.
Abstract : Bacteroides fragilis, an important component of the human gastrointestinal microbiota, can cause lethal extra-intestinal infection upon escape from the gastrointestinal tract. We demonstrated transfer and recombination of large chromosomal segments from B. fragilis HMW615, a multidrug resistant clinical isolate, to B. fragilis 638R. In one example, the transfer of a segment of 435 Kb/356 genes replaced 413 Kb/326 genes of the B. fragilis 638R chromosome. In addition to transfer of antibiotic resistance genes, these transfers (1) replaced complete divergent polysaccharide biosynthesis loci; (2) replaced DNA inversion-controlled intergenic shufflons (that control expression of genes encoding starch utilization system outer membrane proteins) with more complex, divergent shufflons; and (3) introduced additional intergenic shufflons encoding divergent Type 1 restriction/modification systems. Conjugative transposon-like genes within a transferred segment and within a putative integrative conjugative element (ICE5) 45 kb downstream from the transferred segment both encode proteins that may be involved in the observed transfer. These data indicate that chromosomal transfer is a driver of antigenic diversity and nutrient adaptation in Bacteroides that (1) contributes to the dissemination of the extensive B. fragilis pan-genome, (2) allows rapid adaptation to a changing environment and (3) can confer pathogenic characteristics to host symbionts.